2013
DOI: 10.1007/s00894-013-1936-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulations on the possibility of formation of complexes between fluorouracil drug and cucurbit[n]urils: ab initio van der Waals DFT study

Abstract: The binding geometry of fluorouracil/cucurbit[n]urils (CB[n]s) complexes with n = 5-8 is investigated using the first-principles van der Waals density functional (vdW-DF) method, involving full geometry optimization. Such host-guest complexes are typically calculated using conventional DFT method, which significantly underestimates non-local dispersion forces (or vdW contributions) and therefore affects interactions between respected entities. We address here the role of vdW forces for the fluorouracil and CB[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…45 Fayyaz et al [65] Sumanene B3LYP-D3 À17.14 Reichert et al [64] Cucurbit [6]urils PBE-D À19. 37 Sabet and Ganji [61] Zn 12 O 12 B3LYP À18. 41 Zhihong et al [14] Boron carbide nanotube M06-2X À21.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Fayyaz et al [65] Sumanene B3LYP-D3 À17.14 Reichert et al [64] Cucurbit [6]urils PBE-D À19. 37 Sabet and Ganji [61] Zn 12 O 12 B3LYP À18. 41 Zhihong et al [14] Boron carbide nanotube M06-2X À21.…”
Section: Computational Detailsmentioning
confidence: 99%
“…There are indeed several theoretical reports on the interactions of the FU molecule with different nano‐based materials. [ 59–69 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the nature of the interaction between the guest and host cucurbiturils, several theoretical studies have been done . It has been suggested that the nature of interactions between the guest and host cucurbituril are dominated by (i) charge‐dipole interactions, when a cationic host is used (ii) hydrogen bonding interactions between the guest's hydrogen atoms with the carbonyl portal of the host (iii) hydrophobic interactions which exits at the concave cavity of the cucurbituril and (iv) hydrogen interactions between the hydrogen atoms of methylene unit of cucurbituril with guest molecules or an interplay of the above interactions .…”
Section: Introductionmentioning
confidence: 99%
“…the dispersion interaction dramatically affects, as compared to the PBE based calculations, the binding of the host-guest complexes and is crucial to describe such systems". 12 Gavvala et al investigated the interaction of the cardiotonic drug, milrinone, binding in the CB7 molecule with molecular docking (AutoDock software) and optimized the host-guest complex structure with a semiempirical (PM3MM) method. 13 The field of CB7 host-guest chemistry became very exciting recently; many authors pointed out the essence of the "high energy" cavity waters and the importance of other above mentioned interactions during hostguest complex formation.…”
Section: Introductionmentioning
confidence: 99%